Tingkat Kesulitan Pembelajaran Pendidikan Jasmani: Studi Cross Sectional Pada Siswa SMPN 2 Pomala - Haris, Iyan; Yulianto, Ari Gana; Ernawati, Ernawati; Akbar, Muhammad (Jurnal Penelitian Pendidikan, 2023)
This study aims to determine how high the level of learning difficulties of students at SMPN 2 Pomala in learning physical education. This study uses quantitative descriptive research using a survey method with a cross-sectional type. The population in this study were SMPN 2 Pomalaa students who had a total of 140 students from class VII to class IX. Sample withdrawal was carried out by means of Simple rendom sampling (drawing) So the sample in this study amounted to 30 students. The results showed that the level of difficulty in learning physical education in students of SMPN 2 Pomalaa showed that 2 students (6.7%) of students who had difficulty learning physical education in the very low category, 13 students (43.3%) in the low category, 15 students (50.0%) in the medium category, 0 students (0.0%) in the high category, and 0 students (0.0%) in the very high category. The results of this study are expected to be the basis for choosing a learning model that can overcome the level of physical education learning difficulties experienced by students.